INDONESIAN EDUCATION CURRICULUM POLICY: ADAPTATION TO ERA 5.0 AND PREPARATION FOR ERA 6.0 - Annisa Retno Utami; Fitria Haquei; R. Madhakomala (RADJA PUBLIKA, 2024)
This study examines Indonesia's educational curriculum policies in adapting to the 5.0 Era and preparing for the transition to the 6.0 Era. Employing qualitative methods, including interviews with educators, policymakers, and academics alongside a comprehensive literature review, the research identifies key trends, challenges, and opportunities in curriculum development. The findings emphasize the need for integrating advanced technologies, such as artificial intelligence and big data, and strengthening 21st-century skills, including critical thinking and creativity. However, significant challenges, such as infrastructure gaps and limited teacher training, hinder effective implementation. The study underscores the importance of a flexible and adaptive curriculum design, incorporating sustainability and digital literacy while advocating for cross-sector collaboration to bridge existing gaps. These results highlight strategic pathways to create an education system that is innovative, inclusive, and future-ready, addressing global demands while retaining local relevance. This research contributes valuable insights for policymakers and educators in designing curricula that prepare students for the complexities of the 6.0 Era.